2021
DOI: 10.3390/biom11020261
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Chronic Kidney Disease of Unknown Etiology (CKDu): Computational Interaction Analysis of Pesticides and Metabolites with Vital Renal Enzymes

Abstract: Chronic kidney disease of unknown etiology (CKDu) has been recognized as a global non-communicable health issue. There are many proposed risk factors for CKDu and the exact reason is yet to be discovered. Understanding the inhibition or manipulation of vital renal enzymes by pesticides can play a key role in understanding the link between CKDu and pesticides. Even though it is very important to take metabolites into account when investigating the relationship between CKDu and pesticides, there is a lack of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
0
6
0
2
Order By: Relevance
“…The predilection of this disease for agricultural workers is especially shocking. A paper by Rajapaksha, 2021 shows that there are significant interactions between key renal enzymes and commonly used pesticides and their metabolites [ 8 ]. Specifically, this study found that dysfunction caused by quinalphos and chlorpyrifos binding renal 5' adenosine monophosphate-activated protein kinase (AMPK) resulted in fibrosis of interstitial tubules, a common finding in kidney biopsies of MeN patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predilection of this disease for agricultural workers is especially shocking. A paper by Rajapaksha, 2021 shows that there are significant interactions between key renal enzymes and commonly used pesticides and their metabolites [ 8 ]. Specifically, this study found that dysfunction caused by quinalphos and chlorpyrifos binding renal 5' adenosine monophosphate-activated protein kinase (AMPK) resulted in fibrosis of interstitial tubules, a common finding in kidney biopsies of MeN patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found an increased rate of NSAID use in manual laborers, which as a known nephrotoxin, may exacerbate risk from other causative factors in agricultural workers [ 7 ]. De Broe and Vervaet, and Rajapaksha also identified other CKDu hotspots around the world in India, Egypt, Cuba, Bangladesh, Sri Lanka, and France [ 6 , 8 ]. In each hotspot, the same common variables were present: agrochemicals, heat stress, groundwater contamination, and the population at risk was again largely male, agricultural workers.…”
Section: Discussionmentioning
confidence: 99%
“…The eigenvectors, also called principal components (PC), gave the direction of the coordinated movement of the atoms, and the eigenvalues represented the magnitude of the movement along the corresponding eigenvectors [ 53 ]. Thus, PC1 and PC2 were computed, because they contributed more significantly to the PCA analysis [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Figure 4, the eNMA shows the consensus fluctuations are highlighted and reveal a conserved pattern among species and RuBisCO forms (Figure 4a,b). The three isoforms show a greater fluctuation in the N-terminal domain spanning the amino acid residues (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68) between the secondary elements αB and βC (Figure 4a), which are functionally relevant for RbcL. Likewise, RuBisCO form III presents greater fluctuation (≥3 Å) with respect to form I and II (Figure 4a,b).…”
Section: Stability and Flexibility Evaluation Of Rubisco Formsmentioning
confidence: 99%
“…Current literature has yet to demonstrate a conclusive link, with many studies providing contradictory results and meta-analyses not finding any statistically significant risks. 19 , 20 , 21 , 22 , 23 , 24 A more recent hypothesis centers on a putative role for silica nanoparticles. Sugarcane stalks are comprised primarily of naturally occurring amorphous silica, which can be released during routine crop burning.…”
mentioning
confidence: 99%